Critical factors of B2B E-marketplaces among SMEs: the case of agribazaar.com.my / Zazaleena Zakariah, Nursyahidah Alias and Mohd Norafizal Abd Aziz - Zakariah, Zazaleena; Alias, Nursyahidah; Abd Aziz, Mohd Norafizal (Research Management Institute (RMI), 2012)
Electronic marketplaces (e-marketplaces) are new business venues for buying, selling, and supporting customers, products, and services in many industries. The emergence of business-to-business (B2B) e-marketplaces has opened up opportunities for efficient online transactions between companies. Today, many e-marketplaces are still struggling to survive and are trying to understand the characteristics and strategies for becoming successful. This study focuses on B2B e-marketplaces among small and medium enterprises (SMEs) in Malaysia for two key reasons. First, they are important to economic development in developing countries and the second reason to focus on SME's is that they are in a very good position to adapt to new technology as they may be able to adapt faster than larger companies that can be slowed by bureaucracy and stricter staffing hierarchies. As this study is focusing on B2B e-marketplaces among SMEs, AgriBazaar which is a well known e-marketplace for agriculture industries has been chosen. AgriBazaar is a program that has been jointly undertaken by MIMOS Bhd and the Agriculture Department which is focusing on bridging the digital divides, enhancing productivity and competitiveness in the agriculture sector.